Evaluación de la producción forrajera y análisis bromatológico de dos variedades mejoradas de Panicum maximun sometidas a varios intervalos de corte en la época seca - Sellan Vaca, Jonathan Paul (2016)
VIII. SUMMARY This research was carried out at the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7½ of the Babahoyo - Montalvo road. The land is located in the geographical coordinates of 79 ° 32' and Latitude South and 1 ° 49' of Latitude West, with a height of 8 msnm, presents a humid tropical climate, with average annual temperature of 27.7 ° C, an average annual precipitation of 2791.4 mm. The treatments studied were Tanzania (Panicum maximun) and Mombaza (Panicum maximun) pastures, with cut intervals of 20-40-60-80-100; 25-45-65-85 and 30-60-90 days after each cut. In experimental design that was used was BCA in factorial arrangement A x B, where Factor A was constituted by 2 grass varieties, Factor B by the cut intervals in each treatment plus three replicates. Tukey's test was used to estimate the effects of treatment measures. The trial was carried out with the cultural tasks of soil analysis, soil preparation, planting, weed control, fertilization, irrigation, phytosanitary control and harvesting. The evaluated data were plant height, green and dry matter weight, bromatological analysis and economic analysis. From the results obtained it was determined that the highest plant height was obtained in Mombaza grass, with cut intervals of 20-40-60-80-100 days; The highest weight of green matter and dry matter weight was presented in Mombaza grass with cut intervals of 30-60-90 days; The bromatological analysis reached higher values in the Tanzania grass with cut interval of 25-45-65-85 days in terms of total moisture and dry matter, the highest percentage of ash was Tanzania with cut 30-60-90 Days, ethereal extract in Tanzania at cut intervals of 20-40-60-80-100 and 25-45-665-85 days and the highest protein was for Mombaza in cut interval with 20-40-60-80-100 Days and the highest net benefit was reached by Mombaza grass with 30-60-90 day cut intervals of $ 805.72.